The Effect of Meat and Bone Meal on Yield and Herbage Quality in Silage Maize - Anna Nogalska; Marta Borsuk-Stanulewicz; Zenon Nogalski (Applied Sciences)
The purpose of this field study was to assess the impact of meat and bone meal (MBM) on maize. The experimental procedures were as follows: (1) without fertilization; (2) inorganic nitrogen, potassium, and phosphorus; (3) 1.0 Mg·ha−1 MBM; (4) 1.5 Mg·ha−1 MBM; and (5) 2.0 Mg·ha−1 MBM. Each year, MBM was applied before sowing. Nitrogen and potassium were applied at constant rates, and phosphorus was applied at increasing rates of 0.0, 45, 68, and 90 kg·ha−1. The herbage yields were significantly higher in fertilized treatments. Fertilization contributed to a significant increase in the crude protein content of maize herbage. The yield and other herbage parameters were affected by weather conditions and the amount of time that passed since the MBM application. The study demonstrated that the lowest dose of MBM (1.0 Mg·ha−1), which supplied 45 kg phosphorus·ha−1, fully met the phosphorus requirements of maize.